Optimization of the Structure of a Multilayer Cylindrical Shell Under Stability Loss Conditions - Mielczarek, G. (Engineering Transactions, 1995)
The computer program presented here has been devised for minimizing the thickness of a thin cylindrical shell composed of linearly elastic, macro-homogeneous, orthotropic layers, resting on hinged supports and threatened with stability loss under the action of static compressive forces directed along the axis and uniformly distributed along the curvilinear edges of the shell. The optimization process is based on the method for determining the critical loads (Tcr), presented in [1] and on the kinematic broken line theory, and the static distribution theory of lateraI shear stresses.